2019
DOI: 10.1016/j.rmed.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries is associated with lower respiratory tract infections: A population-based cohort study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…For example, one study showed that the incidence of pneumonia increased by 1.2 times per one decayed tooth [ 7 ]. Moreover, a cohort study including young Finnish adults aged 20–27 years suggested that dental caries increased the risk of lower respiratory tract infections even among young adults [ 9 ]. In the field of pediatrics, there have been few studies that focused on the association of respiratory infection with dental caries, but the results of one study showed that dental caries experience was associated with reduced risk of upper respiratory infection in preschool children, results that are not consistent results for adults [ 20 ] and our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study showed that the incidence of pneumonia increased by 1.2 times per one decayed tooth [ 7 ]. Moreover, a cohort study including young Finnish adults aged 20–27 years suggested that dental caries increased the risk of lower respiratory tract infections even among young adults [ 9 ]. In the field of pediatrics, there have been few studies that focused on the association of respiratory infection with dental caries, but the results of one study showed that dental caries experience was associated with reduced risk of upper respiratory infection in preschool children, results that are not consistent results for adults [ 20 ] and our results.…”
Section: Discussionmentioning
confidence: 99%
“…There is fair evidence of an association of respiratory infection, especially pneumonia, with oral health, particularly in elderly adults [ 7 , 8 ]. Even in young adults, dental caries increases the risk of lower respiratory tract infections [ 9 ]. In the field of pediatrics, however, few studies have focused on the association of respiratory infection with dental caries and there have been even fewer studies on the association of dental caries with increased risk of influenza infection.…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries are one of the most common chronic diseases in children and they have been proven to affect systemic health and nutritional status, with a prevalence from 60 to 90% in school children [ 40 ]. Its pathogenesis is multifactorial, comprehensive of environmental, behavioral, and genetic factors, and involves a complex process of enamel dissolution and re-mineralization by organic acids produced by microorganisms within dental plaque [ 8 ].…”
Section: Asthma and Dental Caries/decaymentioning
confidence: 99%
“…In patients with severe dental caries, only the root or residual crown remains, which reduces mastication efficiency; affects digestion and nutrient absorption; and may cause indigestion, gastrointestinal diseases, and other infectious diseases. 2 4 …”
Section: Introductionmentioning
confidence: 99%
“…In patients with severe dental caries, only the root or residual crown remains, which reduces mastication efficiency; affects digestion and nutrient absorption; and may cause indigestion, gastrointestinal diseases, and other infectious diseases. [2][3][4] In China, according to the 4th National Oral Health Survey, the dental caries rates in permanent teeth are 38.5% for 12year-old children, 41.2% for 13-year-old children, 43.3% for 14-year-old children, and 44.4% for 15-year-old children; notably, these caries rates are high and increase with age. 5 It has been reported that dental caries is highly prevalent worldwide, affecting 60% to 90% of school-aged children.…”
Section: Introductionmentioning
confidence: 99%